Predictive Factors Influencing the Perceived Care Burden of Primary Caregivers of School-Age Children with Specific Learning Disabilities - Tiengsomboon, Uraiwan (Journal of Health Sciences and Wellness, 2024)
This study is a descriptive research project aimed at investigating factors that predict theperceived care burden among primary caregivers of school-aged children with specific learning disabilities (SLD). The study, titled "Predictive Factors Influencing the Perceived Care Burden of Primary Caregivers of School-Age Children with Specific Learning Disabilities," was validated for content by experts, with reliability values of 0.91 and 0.86. The Cronbach’s alpha coefficients were calculated to be 0.88 for both. Data collection occurred from December 2022 to March 2023, for a total of four months. The statistical methods used in data analysis included descriptive statistics and Stepwise Multiple Regression. The research findings indicated that the perception of stigma (β=.348), social support (β=.306), and the age of school-aged children with SLD (β=.117) can together predict the perception of care burden of the primary caregiver at 24.9% (Adj. R2= .249, p<.001). Therefore, it is essential that relevant agencies, schools, and public health personnel should be aware of and consider the importance of factors such as the perception of stigma, social support, and the age of children with SLD.